A SHIFT IN THE PRINCIPLE OF BANK SECRECY DUE TO ADVANCEMENT IN INFORMATION TECHNOLOGY - Riswandi, Budi Agus (Varia Justicia, 2020)
Bank secrecy is a conditional legal agreement used by a bank to guarantee the confidentiality of customers' dealing and financial affairs. However, the advancement in information technology, especially in the implementation of electronic systems and transactions across banks, has introduced tremendous changes in the ability of financial institutions to efficiently secure customers? data. This study provides a detailed explanation of the transformation process using the normative method. The result showed a shift in the principle of bank secrecy to data security in the event of a violation.